Pengaruh Motivasi Kerja terhadap Kinerja Karyawan di Courtyard By Marriott Bali Seminyak Resort - Ni Wayan Aprilia Purnama Dewi; Irene Hanna H. Sihombing; I Wayan Jata (Syntax Corporation Indonesia, 2024)
Human resources (HR) play a crucial role in organizations as strategic drivers to face market competition. One important factor affecting performance is work motivation. This reaserch aims to examine the impact of work motivation on employees performance at Courtyard by Marriott Bali Seminyak Resort. The research employs a descriptive quantitative approach, using purposive sampling with 68 respondents. Data analysis is conducted using Simple Linear Regression. The results show that work motivation significantly and positively affects employee performance at Courtyard by Marriott Bali Seminyak Resort. The analysis indicates that work motivation accounts for 65% of the impact on employee performance, with the remaining 35% influenced by factors not covered in this study. Thus, increased employee motivation correlates with improved performance. To enhance employee performance, management support is essential, including increasing employee motivation through appropriate salary, benefits, and health insurance.